2008
DOI: 10.1097/inf.0b013e318178d1ff
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology of Invasive Neonatal Streptococcus agalactiae Isolates in Germany

Abstract: There is a remarkable clonality among invasive GBS isolates that are widely spread geographically and in time; however, no specific clonal lines could be correlated to disease severity and outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 17 publications
0
7
0
1
Order By: Relevance
“…A total of ten different GBS capsular polysaccharide antigenes (Ia, Ib, II-IX) have been described so far; prevalence studies indicated that EOD is associated with Ia, Ib, II, III and V serotypes whereas LOD is associated primarily with type III [4][5][6][7][8]. Other serotypes have been reported mainly in colonization studies, with a predominance of serotypes VI and VIII in Japan and serotype IV in the United Arab Emirates [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…A total of ten different GBS capsular polysaccharide antigenes (Ia, Ib, II-IX) have been described so far; prevalence studies indicated that EOD is associated with Ia, Ib, II, III and V serotypes whereas LOD is associated primarily with type III [4][5][6][7][8]. Other serotypes have been reported mainly in colonization studies, with a predominance of serotypes VI and VIII in Japan and serotype IV in the United Arab Emirates [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Pulsed-field gel electrophoresis (PFGE), used to examine GBS strains, is a powerful technique employed for the classification of microorganisms after digestion of the genomic DNA by restriction enzymes (Benson & Ferrieri 2001, Oliveira et al 2005, von Both et al 2008. Using polymerase chain reaction (PCR), Franken et al (2001) suggested that the scpB and lmb genes (encoding c5a peptidase and laminin binding protein) must exist in GBS strains that infect humans.…”
Section: Group B Streptococci (Gbs) Infections Occur Worldwide Althomentioning
confidence: 99%
“…GBS are classified in serotypes (Ia, Ib and II-VIII) that occur in combination with different protein antigens (alpha, beta and rib) (Dmitriev et al 2001). Currently, serotypes Ia, III and V are the most common in many countries (Duarte et al 2005, Fluegge et al 2005, Bergseng et al 2008, Poyart et al 2008, von Both et al 2008.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple surveillance studies have indicated that all serotypes are able to colonize the vagina and perianal region of pregnant women, but five serotypes (Ia, Ib, II, III, and V) are predominant and are also the most frequent in human infections (8-12). In particular, serotype III accounts for 30 to 76% of neonatal disease cases (13,14). The use of multilocus sequence typing (MLST) allowed the classification of GBS isolates independently from their capsular serotypes and the identification of the bacterial genogroups more often associated with invasive infections in newborns (15).…”
mentioning
confidence: 99%